2017
DOI: 10.1093/neuros/nyx326
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Interspinous Spacer vs Decompression in Patients with Neurogenic Claudication: An Alternative in Selected Patients?

Abstract: BACKGROUNDStandalone interspinous process devices (IPDs) to treat degenerative lumbar spinal stenosis with neurogenic intermittent claudication (NIC) have shown ambiguous results in the literature.OBJECTIVETo show that a minimally invasive percutaneous IPD is safe and noninferior to standalone decompressive surgery (SDS) for patients with degenerative lumbar spinal stenosis with NIC.METHODSA multicenter, international, randomized, controlled trial (RCT) was con- ducted. One hundred sixty-three patients, enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…Likely also postoperatively, alMRI provides a more realistic image of the spine morphology during spinal loading, compared to conventional MRI. Hence, the insufficient radiological effects of the IPD in the current study provide a reasonable patho-anatomical explanation to reported clinical treatment failure and high reoperation rates [8][9][10][11].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Likely also postoperatively, alMRI provides a more realistic image of the spine morphology during spinal loading, compared to conventional MRI. Hence, the insufficient radiological effects of the IPD in the current study provide a reasonable patho-anatomical explanation to reported clinical treatment failure and high reoperation rates [8][9][10][11].…”
Section: Discussionmentioning
confidence: 61%
“…Contrarily, the ODS group displayed a DSCSA increase in changing from an absolute stenosis preoperatively to close to what is considered normal DSCSA postoperatively ( Table 2). The failure of the IPD to show radiological improvement postoperatively in alMRI might, at least to some extent, explain the general lack of long-term functionality and high reported reoperation rates among LSS patients treated with IPD [8][9][10][11]23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the management of lumbar spinal stenosis, a recent randomized controlled trial showed that minimally invasive percutaneous interspinous process devices may be effective in the treatment of neurogenic claudication. 230 Image-guided minimally invasive percutaneous techniques for drilling of osteochondral lesions were described for the talus, 231 knee, 232 and even the sacroiliac joint. 233 Given the general move toward minimally invasive procedures, these techniques may hold potential for the future.…”
Section: Percutaneous Fixation and Orthopaedic Implantsmentioning
confidence: 99%